Effect of β-PVDF Piezoelectric Transducers’ positioning on the acoustic streaming flows - Catarino, Susana Oliveira (2014)
This paper reports the numerical and experimental analysis of the acoustic streaming effect in a fluidic domain. The actuation of a piezoelectric transducer generates acoustic waves that propagate to the fluids, generating pressure gradients that induce the flow. The number and positioning of the transducers affect the pressure gradients and, consequently, the resultant flow profile. Two actuation conditions were considered: (1) acoustic streaming generated by a 28 μm thick β-poly(vinylidene fluoride) (β-PVDF) piezoelectric transducer placed asymmetrically relative to the fluidic domain and (2) acoustic streaming generated by two 28 μm thick β-PVDF piezoelectric transducers placed perpendicularly to each other. The transducers were fixed to the lower left corner of a poly(methyl methacrylate) (PMMA)cuvette and were actuated with a 24 Vpp and 34.2 MHz sinusoidal voltage. The results show that the number of transducers and their positioning affects the shape and number of recirculation areas in the acoustic streaming flows. The obtained global flows show great potential for mixing and pumping, being an alternative to the previous geometries studied by the authors, namely, a single transducer placed symmetrically under a fluidic domain.